Classifiers, partitions, and measurements: Exploring the syntax and semantics of sortal classifiers. Issue 1 (10th July 2019) - Bale, Alan; Coon, Jessica; López, Nicolás Arcos
Abstract : In many languages, measure terms like item and kilo, as in two items of furniture and two kilos of rice, can be used either to partition the nominal denotation into countable units, or to measure a denotation without inducing a partition. These two types of measurements are associated with two different syntactic structures: a partition-structure where the measure term forms a constituent with the noun independent of the numeral, and a measure-structure where the measure term forms a constituent with the numeral. Some researchers have claimed that in classifier languages, sortal classifiers are (most often) used in a partition-structure—hence the classifier forms a constituent with the noun independent of the numeral. In contrast, non-sortal classifiers (i.e., measure classifiers) are often used in a measure-structure—the classifier forms a constituent with the numeral and this constituent modifies the noun. Contrary to these claims, we demonstrate that in Ch'ol (Mayan) all classifiers, sortal and non-sortal alike, are used in a measure-structure independent of the types of readings that are available with respect to the measure term. As a result, the correlation between partitioned meanings and partition-structures is not universal. We review several diagnostics that support this claim. These diagnostics can be used as a template to test the constituency structure in other classifier languages.